Intra-Strain Genetic Variation of Platyfish (Xiphophorus maculatus) Strains Determines Tumorigenic Trajectory - Lu, Yuan; Olivas, Taryn J.; Boswell, Mikki; Boswell, William; Warren, Wes C.; Schartl, Manfred; Walter, Ronald B. (Frontiers in Genetics, 2020)
Xiphophorus interspecies hybrids represent a valuable model system to study heritable tumorigenesis, and the only model system that exhibits both spontaneous and inducible tumors. Types of tumorigenesis depend on the specific pedigree of the parental species, X. maculatus, utilized to produce interspecies hybrids. Although the ancestors of the two currently used X. maculatus parental lines, Jp163 A and Jp163 B, were originally siblings produced by the same mother, backcross interspecies hybrid progeny between X. hellerii and X. maculatus Jp163 A develop spontaneous melanoma initiating at the dorsal fin due to segregation of an oncogene and a regulator encoded by the X. maculatus genome, while the backcross hybrid progeny with X. hellerii or X. couchianus and Jp163 B exhibit melanoma on the flanks of their bodies, especially after treatment with ultraviolet light. Therefore, dissecting the genetic differences between these two closely related lines may lead to better understanding of functional molecular differences associated with tumorigenic mechanisms. For this purpose, comparative genomic analyses were undertaken to establish genetic variants between these two X. maculatus lines. Surprisingly, given the heritage of these two fish lines, we found genetic variants are clustered together in select chromosomal regions. Among these variants are non-synonymous mutations located in 381 genes. The non-random distribution of genetic variants between these two may highlight ancestral chromosomal recombination patterns that became fixed during subsequent inbreeding. Employing comparative transcriptomics, we also determined differences in the skin transcriptional landscape between the two lines. The genetic differences observed are associated with pathways highlighting fundamental cellular functions including inter-cellular and microenvironment-cellular interactions, and DNA repair. These results collectively lead to the conclusion that diverged functional genetic baselines are present between Jp163 A and B strains. Further, disruption of these fixed genetic baselines in the hybrids may give rise to spontaneous or inducible mechanisms of tumorigenesis.